Inhibition of angiogenesis and regenerative lung growth in Lepob/ob mice through adiponectin-VEGF/VEGFR2 signaling - Hunyenyiwa, Tendai; Kyi, Priscilla; Scheer, Mikaela; Joshi, Mrudula; Gasparri, Mario; Mammoto, Tadanori; Mammoto, Akiko (Frontiers in Cardiovascular Medicine, 2024)
Obesity is associated with impairment of wound healing and tissue regeneration. Angiogenesis, the formation of new blood capillaries, plays a key role in regenerative lung growth after unilateral pneumonectomy (PNX). We have reported that obesity inhibits angiogenesis. The effects of obesity on post-PNX lung vascular and alveolar regeneration remain unclear. Regenerative lung growth and expression of vascular endothelial growth factor (VEGF) and its receptor VEGFR2 induced after PNX are inhibited in Lep ob/ob obese mice. The levels of adiponectin that exhibits pro-angiogenic and vascular protective properties increase after unilateral PNX, while the effects are attenuated in Lep ob/ob obese mice. Post-PNX regenerative lung growth and increases in the levels of VEGF and VEGFR2 are inhibited in adiponectin knockout mice.Adiponectin stimulates angiogenic activities in human lung endothelial cells (ECs), which is inhibited by decreasing the levels of transcription factor Twist1.Adiponectin agonist, AdipoRon restores post-PNX lung growth and vascular and alveolar regeneration in Lep ob/ob obese mice. These findings suggest that obesity impairs lung vascular and alveolar regeneration and adiponectin is one of the key factors to improve lung regeneration in obese people.